Risk of Nonspine Fractures in Older Adults with Sarcopenia, Low Bone Mass, or Both. Issue 9 (27th August 2015) - Chalhoub, Didier; Cawthon, Peggy M.; Ensrud, Kristine E.; Stefanick, Marcia L.; Kado, Deborah M.; Boudreau, Robert; Greenspan, Susan; Newman, Anne B.; Zmuda, Joseph; Orwoll, Eric S.; Cauley, Jane A.; the Osteoporotic Fractures in Men Study Research Group
<x xml:space="preserve">Abstract</x> Objectives To test the hypothesis that men and women with low bone mineral density (BMD) and sarcopenia have a higher risk of fracture than those with only one or neither conditions. Design The Osteoporotic Fractures in Men Study and the Study of Osteoporotic Fractures in women are prospective observational studies with a mean follow up of 9 (2000–2012) and 8 years (1997–2009), respectively. Setting U.S. clinical centers. Participants Men (n = 5, 544; mean age 73.7) and women (n = 1, 114; mean age 77.6) aged 65 and older, able to walk without assistance, and without bilateral hip replacement. Measurements Sarcopenia was defined as low appendicular lean mass plus slowness or weakness and low BMD according to the World Health Organization definition of a T‐score less than –1.0. Participants were classified as having normal BMD and no sarcopenia (3, 367 men, 308 women), sarcopenia only (79 men, 48 women), low BMD only (1, 986 men, 626 women), and low BMD and sarcopenia (112 men, 132 women). Results Men with low BMD and sarcopenia (hazard ratio (HR)=3.79, 95% confidence interval (CI)=2.65–5.41) and men with low BMD only (HR=1.67, 95% CI=1.45–1.93) but not men with sarcopenia only (HR=1.14, 95% CI=0.62–2.09) had greater risk of fracture than men with normal BMD and no sarcopenia. Women with low BMD and sarcopenia (HR=2.27, 95% CI=1.37–3.76) and women with low BMD alone (HR=2.62, 95% CI=1.74–3.95), but not women with only sarcopenia, had greater risk of fracture than women with normal BMD and no sarcopenia. Conclusion Men with low BMD and sarcopenia are at especially high risk of fracture. Sarcopenia alone did not increase fracture risk in either group.